Dialektika antara Aliran Hukum Alam dan Hukum Positif dan Relevansi dengan Hukum Islam - Hajar M. (Fakultas Hukum Universitas Islam Indonesia, 2013)
The main research questions in this study are: First, how is the dialectic between the positive law and the natural law? and second, how is its relevance with the Islamic law? The purpose of this study is to understand the dialectic between the positive law and the natural law and its relevance with the Islamic law. The method used in this study is philosophycal approach. The discussion is presented using descriptive analityc method which is then analyzed using juridical qualitative and juridical normative methods. The result concludes that: First, the natural law is both based on the principle of justice and related with the proper law. The positive law is inspired by the insight on the opposite law. The positive law is separated fron the justice and ethics, while the natural law is ideal and higher in its position as the standard of justice. Since the natural law is based on the conscience, it cannot prevail. Second, Islamic law consisting of revelations as well as positive law and natural law can be combined yet still harmonious in nature.